1996
DOI: 10.1002/aic.690420213
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization of phenanthrene from toluene with carbon dioxide by the GAS process

Abstract: The crystallization of phenanthrene fiom toluene with carbon dioxide as the antisolvent gas is described. In the GAS process, a pressurized

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 7 publications
1
32
0
Order By: Relevance
“…In this mode, the slopes of the initial part of the pressure profile as well as the duration of the crystal growth period are the control parameters. In modifications of this basic method suggested by Berends et al (77), pressure was raised linearly until saturation and turbidity were reached. A ''pulse period'' was then performed to favor nuclei creation.…”
Section: Influence Of Process Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…In this mode, the slopes of the initial part of the pressure profile as well as the duration of the crystal growth period are the control parameters. In modifications of this basic method suggested by Berends et al (77), pressure was raised linearly until saturation and turbidity were reached. A ''pulse period'' was then performed to favor nuclei creation.…”
Section: Influence Of Process Parametersmentioning
confidence: 99%
“…However, it was pointed out that a high stirrer frequency may be responsible of significant attrition (77).…”
Section: Influence Of Process Parametersmentioning
confidence: 99%
“…at low CO 2 introduction rate. Relation between saturation behaviour and crystal growth has been enlighted by several authors [14][15][16][17]. As example, Tay et al [15] showed that, depending on the type of solvent and solute, precipitation may occur by catastrophic or heterogeneous nucleation or even may not happen.…”
Section: Introductionmentioning
confidence: 99%
“…The technology for CO 2 separation is well established because CO 2 has a great number of industrial applications including in dry ice production, automatic welding, carbonation of beverages, plant cultivation, chemicals manufacture (e.g., urea, MgCO 3 , BaCO 3 , SrCO 3 ), and enhanced oil recovery. Separation technologies include adsorption (Karger et al, 1973;King, 1980), membrane separation (Stern, 1994;Baker, 2002;Wind et al, 2003), extraction and absorption (Danckwerts, 1979;Versteeg and Swaaij, 1988;Vá zquez et al, 1997), recrystallization (Berends et al, 1996;Yoo et al, 1999) and ion shift (Kusakabe et al, 1998;Shiflett and Yokozeki, 2005). Among these, adsorption, membrane separation, and extraction and absorption are thought to have potential industrial applications, but each process has advantages and disadvantages in terms of thermodynamics, chemical paths and economic viability.…”
Section: Trends In Co 2 Storage and Capturementioning
confidence: 99%